Applications of Medical Physics in Cancer Diagnosis and Treatment - Radhi, Hussein Fleih Hassan; Sultan, Ali Hassan Mohammed; Chemig, Noor Farhan Joudah; Abbas, Bayraq Abbas Abdul Mahdi; Yousif Waheed Yousif Tleel, (American Journal of Biomedicine and Pharmacy, 2025)
Medical physics plays a crucial role in cancer diagnosis and treatment, particularly in the application of radiotherapy and advanced imaging techniques. Despite significant technological advancements, challenges remain in optimizing radiation delivery while minimizing damage to healthy tissues. This study examines the latest developments in carbon ion therapy, dosimetry, and medical imaging, employing a multidisciplinary approach that integrates computational modeling, experimental studies, and clinical assessments. Findings highlight the effectiveness of high-energy ion beams in targeting tumors with precision, improving treatment outcomes, and reducing side effects. The results emphasize the need for continued innovation in radiation safety protocols, personalized treatment planning, and enhanced imaging methodologies to advance cancer care.